The Role of Telegram Channels in the News Media Ecosystem: Between Freedom and Moderation - Remeika, Darius (Information & Media, 2025)
Telegram, an unmoderated digital platform, presents challenges to both democracy and authoritarian systems. The platform attracts activists, journalists, and citizens seeking anonymity to protect themselves from government surveillance or to avoid social media with stricter moderation rules. The aim of this article is to examine Telegram channels and their role in the modern media ecosystem through the normative media roles – monitoring, facilitative, collaborative, and radical – thus drawing attention to the opportunities and threats to democracy that this platform creates. The article summarizes research in an attempt to reveal the multifaceted functionality of Telegram channels. The study reveals that Telegram can successfully perform the function of a watchdog in a monitoring role, create a safe environment for discussion, while empowering unheard and marginalized voices in society, collaborate with government institutions, ensure public safety or promote resistance to the hegemony of power, thereby creating mobilizing communication and operationalizing a resistance movement. However, Telegram’s technical solutions and lack of moderation create sphere for the spread of disinformation and manipulation, as well as set up conditions for extremism, and fail to effectively prevent criminal activity.
Keywords: unmoderated platform; digital platform; Telegram; media roles